Recent Advances Related To Rape Laws (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Uncontrolled increase in rape incidences all over India especially in Delhi, ironically called a ‘Rape Capital’. The number of Downloaded From IP - 59.178.18.222 on dated 13-Sep-2024 alleged rapes reported in 2004 crossed the 500 mark, for the first time in the Capital’s history1 spurt in incidences of rape,  especially against foreigners attracted attention of media both at national and international levels. A 36 years old Swiss Diplomat  Members Copy, Not for Commercial Sale  was abducted and raped in her car on October 14, 2003. On March 15, 2004 a businessman at Deer Park in Safdarjung Enclave  www.IndianJournals.com  allegedly raped a 20 years old Fiji student. On March 17, 2004 a 59 years old Australian tourist was allegedly sexually assaulted  and murdered by a taxi driver near IGI Airport, barely a couple of hours after she landed from Brisbane.2  This paper deals with recent advances made in Indian rape laws in 2005, a brief review of amendments done in 1983 and role of DNA profile in rape cases, their impact in controlling the most heinous crime against humanity i.e. ‘Rape’.
Keywords: Crime; Heinous; Human Rights; Humanity; Rape